PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN BERPIKIR KREATIF DAN PRESTASI BELAJAR - Martina Putri (DIADIK, 2023)
The purpose of this study is to describe (1) the application of the inquiry learning model can improve students' creative thinking in class X IPS MAN Lebong, (2) the application of the inquiry learning model can improve student achievement in class X IPS MAN Lebong, and (3) the effectiveness of the application of the learning model. inquiry can improve student achievement in the subject of Sociology in class X IPS MAN Lebong. The research design used is Classroom Action Research combined with quasi-experimental. The subjects of this study were students of class X IPS, 1 as a PTK class, class X IPS MAN 01 Lebong as an experimental class, while class X IPS MAN 02 Lebong as a control class. The instruments used are observation sheets, pre-test and post-test. The data analysis technique used the formula for the average percentage value of classical learning completeness and T- test. The results showed that (1) the application of the inquiry learning model can improve students' creative thinking in class X IPS MAN Lebong, (2) the application of the inquiry learning model can improve student achievement in class X IPS MAN Lebong, and (3) the effectiveness of the application of the learning model. inquiry can improve student achievement in the subject of Sociology in class X IPS MAN Lebong.